Intentional Non-Adherence to Medications among HIV Positive Alcohol Drinkers: Prospective Study of Interactive Toxicity Beliefs - Kalichman, Seth C. (Springer-Verlag, 2012)
BACKGROUND: Antiretroviral therapy (ART) adherence is key to successful treatment of HIV infection and alcohol is a known barrier to adherence. Beyond intoxication, ART adherence is impacted by beliefs that mixing alcohol and medications is toxic. PURPOSE: To examine prospective relationships of factors contributing to intentional medication non-adherence when drinking. METHODS: People who both receive ART and drink alcohol (N = 178) were enrolled in a 12-month prospective cohort study that monitored beliefs about the hazards of mixing ART with alcohol (interactive toxicity beliefs), alcohol consumption using electronic daily diaries, ART adherence assessed by both unannounced pill counts and self-report, and chart-abstracted HIV viral load. RESULTS: Participants who reported skipping or stopping their ART when drinking (N = 90, 51 %) demonstrated significantly poorer ART adherence, were less likely to be viral suppressed, and more likely to have CD4 counts under 200/cc(3). Day-level analyses showed that participants who endorsed interactive toxicity beliefs were significantly more likely to miss medications on drinking days. CONCLUSIONS: Confirming earlier cross-sectional studies, the current findings from a prospective cohort show that a substantial number of people intentionally skip or stop their medications when drinking. Interventions are needed to correct alcohol-related interactive toxicity misinformation and promote adherence among alcohol drinkers.